2009
DOI: 10.2741/3249
|View full text |Cite
|
Sign up to set email alerts
|

IGF-IR in neuroprotection and brain tumors

Abstract: The IGF-IR is a multifunctional tyrosine kinase receptor involved in several biological processes including cell proliferation, differentiation, DNA repair, and cell survival. In the brain IGF-I plays a critical role during embryonic and early postnatal development. In the mature brain, IGF-I binding sites have been found in different regions of the brain, and multiple reports confirmed a strong neuroprotective action of the IGF-IR against different pro-apoptotic insults. When the IGF-IR signaling system is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 263 publications
(273 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, overexpression of components of the IGF pathway is observed in medulloblastoma, ependymoma, glioblastoma, and astrocytoma. Several reports have shown that the IGF-I receptor signaling pathway is highly active in medulloblastoma cell lines, animal models, and human tumor tissues (36). Finally, an effect of accelerated growth on carcinogenesis is supported by the increased risk for cancer observed in overgrowth syndromes, such as Beckwith-Wiedemann (37), Soto (38), and acromegaly (39).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, overexpression of components of the IGF pathway is observed in medulloblastoma, ependymoma, glioblastoma, and astrocytoma. Several reports have shown that the IGF-I receptor signaling pathway is highly active in medulloblastoma cell lines, animal models, and human tumor tissues (36). Finally, an effect of accelerated growth on carcinogenesis is supported by the increased risk for cancer observed in overgrowth syndromes, such as Beckwith-Wiedemann (37), Soto (38), and acromegaly (39).…”
Section: Discussionmentioning
confidence: 90%
“…A third explanation might be that the intrauterine presence of a CNS tumor could influence the overall growth rate of the fetus through endogenous hormonal mechanisms (36).…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly because of its multiple antiapoptotic signals (Baserga et al, 1997a; Peruzzi et al, 1999), the role of IGF-IR in protecting fetal brain tissue during development (Gualco et al, 2009a,b), and the supportive role of IGF-I in maintaining growth and survival of oli-godenrocyte progenitors (Arsenijevic et al, 2001; Hsieh et al, 2004). In addition to the antiapoptotic action of IGF-IR, IGF-I treatment can also counteract ROS accumulation in HG-treated mesanglial cells (Kang et al, 2003b; Yang et al, 2005), and HG-induced accumulation of intracellular ROS was partially inhibited by IGFI in PC12 neuron-like cells and in rat cortical neurons (this paper; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Normal IGF-signaling is critical during cerebellar development and treatment with IGF-1 can protect GCP from pathological cell death (18 -20). The importance of IGFsignaling in tumorigenesis and progression of Med and other CNS malignancies is also well-established (21)(22)(23). In transgenic models of Med, disruption of the IGF and sonic hedgehog signaling pathways act synergistically to increase Med incidence (24).…”
mentioning
confidence: 96%
“…In transgenic models of Med, disruption of the IGF and sonic hedgehog signaling pathways act synergistically to increase Med incidence (24). In human Med, increased expression of IGF1R and increased IGF-signaling are associated with increased tumor growth and decreased apoptosis (21,25). Inhibition of IGF1R has also been shown to decrease Med growth and to increase sensitivity of Med cells to cytotoxic chemotherapeutics (26,27).…”
mentioning
confidence: 98%